IMPLEMENTASI PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN BAHASA INDONESIA MELALUI STEAM PADA SISWA KELAS VIII SMP MUHAMMADIYAH PLAYEN - Romantisa Ajeng Sabila Fatmawati; Hermanto; Dedi Wijayanti (JURNAL KOULUTUS, 2026)
This study aims to describe the steps of preparation, implementation, evaluation, as well as challenges and how to overcome them in the application of Deep Learning using the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in teaching Indonesian language regarding poetry texts. The approach applied is descriptive qualitative with a focus on Indonesian language teachers and eighth grade students of Muhammadiyah Playen Middle School. The research findings state that: (1) Preparation is carried out by integrating the Independent Curriculum into teaching modules that link scientific phenomena with literary materials. (2) Implementation applies the principles of attentive, meaningful, and enjoyable learning through poetry creation projects based on natural phenomena and digital media. (3) Evaluation includes initial assessment, formative assessment, and summative assessment in the form of poetry works. (4) The main obstacle faced is time management, which is resolved by compiling a planned activity matrix.